Preparing Library and Information Science Students for Orally Based Communities - Kigongo-Bukenya, I. M.N. (World Library and Information Congress, 2010)
Article 19 of the Universal Declaration of Human Rights (UDHR, 1948) proclaims that every human being has a right to seek information. Notwithstanding this Universal Declaration, many people in the world are still deprived of information because of poverty, illiteracy or lack of infrastructure. This paper explores the hypothesis that production of information professionals with orientation to serve the orally based communities is one of the solutions to accessing information services to orally based communities who happen to be deprived of this right in developing countries for example 31% of Ugandans were still being deprived of this right through illiteracy (Peoples Daily On-line, 2005). It is ironical that information provision is hardly guaranteed in the rural areas where the majorities who participate in agriculture-the major contributors to the National GDP-do reside.